2011
DOI: 10.1159/000334122
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity from the Combined Application of Poly(I:C) and Chemotherapeutics in Human Metastatic Pharyngeal Cell Lines

Abstract: Background: Toll-like receptor 3 (TLR3) activation in tumor cells induces apoptosis. We investigated the effect of TLR3 ligand (poly(I:C)) in combination with chemotherapeutics applied to human pharyngeal carcinoma cells as a possible antitumor therapy. Methods:Human pharyngeal cancer cell lines were studied (FaDu and Detroit 562). Cytotoxicity assays and apoptosis assays (annexin V staining and caspase 3/7 activity measurements) were used to investigate the cytotoxic effects. By using TLR3 siRNA we confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…The combined use of TLR3 activation with poly(I:C) and cisplatin in cancer has been previously investigated. We and the others have shown that poly(I:C) and cisplatin act synergistically to induce cell death [16,21,22]. The results of a very recent study confirmed our hypothesis and showed that pre-treatment with poly(I:C) increased the amount of cisplatin in the cytoplasm, and greatly increased the low-dose cisplatin-induced cell death in TLR3-and caspase-3-dependent manner [21].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The combined use of TLR3 activation with poly(I:C) and cisplatin in cancer has been previously investigated. We and the others have shown that poly(I:C) and cisplatin act synergistically to induce cell death [16,21,22]. The results of a very recent study confirmed our hypothesis and showed that pre-treatment with poly(I:C) increased the amount of cisplatin in the cytoplasm, and greatly increased the low-dose cisplatin-induced cell death in TLR3-and caspase-3-dependent manner [21].…”
Section: Discussionsupporting
confidence: 84%
“…Caspase 3/7 enzyme activity was determined using the Caspase-Glo 3/7 assay (Promega, Madison, USA) as previously described [16]. Briefly, SQ20B cells at a concentration of 1.5 ×10 4 cells/well were plated in a whitewalled 96-well plate in 100 μl culture medium and treated with 10 µg/ml poly(I:C) or 1µM cisplatin for 45 minutes, irradiated and caspase 3/7 activity was determined after 24 hours.…”
Section: Measurement Of Caspase 3/7 Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…As our experimental results showed, poly I:C also elevated the expression levels of RIG-1 and MDA-5 along with IFN-β production, and this effect was stronger with impaired TLR3- With attempts to optimize practical results, combination chemotherapy regimens for neoplastic cell treatment are frequently favored over single agents. Recent studies display that poly I:C in combination with anticancer agents like cycloheximide, 5-fluorouracil, or PTX for chemo-immunotherapy appears to offer promising effects (Jiang et al, 2008;Matijević, Kirinec, & Pavelić, 2011;Park et al, 2012)…”
Section: Poly I:c Specifically Impairs the Viability Of The Ptx-resistant Cell Line Hct-8/ptxmentioning
confidence: 99%
“…In a somehow paradoxical manner, many investigators have emphasized the role of TLR3 as a factor of vulnerability for malignant cells. Initially Poly(I:C) was used as an artificial ligand of TLR3 and was shown in several studies to induce apoptosis of various types of malignant cells in vitro [12, 14, 16, 17]. However, these studies have met two limitations.…”
Section: Introductionmentioning
confidence: 99%